2017
DOI: 10.5194/acp-17-8081-2017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aerosols and clouds on decadal trends in all-sky solar radiation over the Netherlands (1966–2015)

Abstract: Abstract.A 50-year hourly data set of global shortwave radiation, cloudiness and visibility over the Netherlands was used to quantify the contribution of aerosols and clouds to the trend in yearly-averaged all-sky radiation (1.81 ± 1.07 W m −2 decade −1 ). Yearly-averaged clearsky and cloud-base radiation data show large year-to-year fluctuations caused by yearly changes in the occurrence of clear and cloudy periods and cannot be used for trend analysis. Therefore, proxy clear-sky and cloud-base radiations wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Previous studies (Boers et al, 2017;Pfeifroth et al, 2018;Wang, Dickinson, et al, 2012) have confirmed that clouds and aerosols are the dominant factors in the variation in R s . Comparatively, radiatively active gases Figure 10.…”
Section: Impact Factors Of Variability In R Smentioning
confidence: 78%
“…Previous studies (Boers et al, 2017;Pfeifroth et al, 2018;Wang, Dickinson, et al, 2012) have confirmed that clouds and aerosols are the dominant factors in the variation in R s . Comparatively, radiatively active gases Figure 10.…”
Section: Impact Factors Of Variability In R Smentioning
confidence: 78%
“…From the observations it appears that the yearly average of solar radiation at the surface has significantly increased over the years (Figure 8). The increase relates to a cleaner atmosphere and due to different cloud properties [2], and not because the sun has increased its energy. The increase of solar radiation at the surface is of course good news for solar energy applications.…”
Section: Advancing the Understanding Of Atmospheric Processesmentioning
confidence: 99%
“…Since marine emissions were not regulated during 1990-2010 (Eyring et al, 2005;Aksoyoglu et al, 2016), we did not adjust the AOD (i.e., p f = 1) over the sea and ocean (for PHOT1, PHOT2 and PHOT3 scenarios), where the contribution of ship emissions to the PM 2.5 concentrations is more significant (up to 50 %) compared to continental Europe (up to 10 %) as shown by for the summer of 2006. This way, we expect that the photolysis rate sensitivity tests will represent in general more consistently the AOD conditions of 1990, even though this approach might be conservative as the European maritime AOD trends suggest a decline (significant at the 95 or 99 % level) since the early/mid-1990s (Mishchenko et al, 2007;Cermak et al, 2010;Li et al, 2014a). E. Oikonomakis et al: Solar "brightening" impact on summer surface ozone 9747 2.3.2 Impact via BVOC emissions…”
Section: Combo_nomentioning
confidence: 99%